A population-based case–control study of the association between cervical spondylosis and tinnitus. (1st March 2021) - Cheng, Yen-Fu; Xirasagar, Sudha; Yang, Tzong-Hann; Wu, Chuan-Song; Kuo, Nai-Wen; Lin, Herng-Ching
Abstract: Objective: This population-based study aimed to study the association between tinnitus and cervical spondylosis. Design: A case–control study. Study sample: We retrieved data from the Taiwan Longitudinal Health Insurance Database. We identified 2465 patients with tinnitus (cases) and 7395 comparison patients by propensity score matching. Multivariable logistic regressions were conducted to estimate the odds (OR) of a diagnosis of cervical spondylosis preceding the tinnitus diagnosis relative to controls. Results: We found that 1596 (16.19%) of 9860 sample patients had received a diagnosis of cervical spondylosis before the index date, significantly different between the tinnitus group and control group (17.20% vs. 15.85%, p < 0.001). Logistic regression analysis showed an adjusted OR for prior cervical spondylosis of 1.235 for cases vs. controls (95% confidence interval [CI]: 1.088–1.402). Further, the adjusted ORs were 1.246 (95% CI: 1.041–1.491) and 1.356 (95% CI: 1.016–1.811), respectively, among patients aged 45 ∼ 64 and >64 groups. No difference in cervical spondylosis likelihood between cases and controls was found among patients aged 18 ∼ 44 groups. Conclusions: In conclusion, the study shows a positive association between cervical spondylosis and tinnitus. The findings call for greater awareness among physicians about a possible somatosensory component of cervical spine function which may contribute to tinnitus.